Ballmilling-assisted synthesis and electrochemical performance of LiFePO4/C for lithium-ion battery adopting citric acid as carbon precursor - Zhang, D.; Yu, X.; Wang, Y.; Cai, R.; Shao, Zongping; Liao, X.; Ma, Z. (The Electrochemical Society, Inc, 2009)
LiFePO4/C composite cathode for secondary lithium-ion battery was synthesized via a mechanochemical activation/sintering process adopting citric acid (CA) as carbon source. The carbon formation process, optimal carbon content, and electrochemical performance of the as-synthesized powders are investigated by thermogravimetry-differential scanning calorimetric analyzer, X-ray powder diffraction, CO2 -temperature-programmed desorption (TPD), temperature-programmed reaction, scanning electron microscopy, impedance spectroscopy, and charge-discharge characterizations. The thermal decomposition of CA was found to conduct in two successive steps: It is first cracked to CHx between 50 and 400°C and then further decomposed to carbon at YYY; both temperatures are lower than that of the sucrose. CO2 -TPD characterization demonstrated that 5.0, 6.0, 6.75, and 8.0 wt % of CA applied during the synthesis resulted in carbon contents of 1.81, 3.23, 3.63, and 4.04 wt % in the final product, respectively. The cathode with its precursor containing 6.0 wt % CA shows highest discharge capacities of ~153 and 92 mA h g-1 at 1C and 20C rates, respectively, which are comparable to the best results reported for a LiFePO4/C cathode. It then highly appreciates the mechanochemical activation/sintering process with CA as the carbon source in the synthesis of high performance LiFePO4 /C. © 2009 The Electrochemical Society.